1999
DOI: 10.1557/s1092578300000624
|View full text |Cite
|
Sign up to set email alerts
|

The growth rate evolution versus substrate temperature and V/III ratio during GaN MBE using ammonia

Abstract: The growth rate evolution versus V/III ratio and substrate temperature was studied by means of optical reflectivity during MBE of GaN layers using NH 3 as nitrogen source. The GaN desorption becomes observable at temperatures above 800 ° C and causes the reduction of growth rate accompanied with the surface roughening at temperatures above 850-870 ° C. Unlike GaAs, which evaporates in accordance with the action mass law, the desorption rate of GaN is found to be almost independent of V/III ratio within the N-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Therefore, the optimum GaN growth temperature can be determined as a threshold value corresponding to a temperature approaching the GaN thermal decomposition temperature. [33][34][35] In our experiment, for an NH 3 flow of 100 cm 3 min −1 , this temperature was determined to be T g = 945 °C, and these conditions were used for the growth of the AlGaN buffer as well as the barrier layers.…”
Section: Growth Of Hemt Heterostructures and Their 2deg Propertiesmentioning
confidence: 99%
“…Therefore, the optimum GaN growth temperature can be determined as a threshold value corresponding to a temperature approaching the GaN thermal decomposition temperature. [33][34][35] In our experiment, for an NH 3 flow of 100 cm 3 min −1 , this temperature was determined to be T g = 945 °C, and these conditions were used for the growth of the AlGaN buffer as well as the barrier layers.…”
Section: Growth Of Hemt Heterostructures and Their 2deg Propertiesmentioning
confidence: 99%
“…Температура роста слоев AlGaN в серии варьировалась от 860 до 950 °С. Известно, что шероховатость поверхности и скорость роста слоев GaN чувствительны к температуре роста вследствие влияния термического разложения GaN [8,9] Влияние температуры роста на локализацию неравновесных носителей в слоях AlGaN исследовалось путем измерения стоксова сдвига, который определялся как энергетический зазор между положением полосы ФЛ и краем поглощения, оцененного по спектру пропускания [10]. Полученные результаты приведены на рис.…”
Section: методика проведения экспериментаunclassified
“… 29 It is well-known that critical parameters in all MBE growth processes are the III/V elements ratio and substrate temperature. Many studies showed that temperature has a vital influence on the crystal quality and surface roughness 30 , 31 and on defect states and stress relaxation. 32 MBE growth of GaN at high temperatures leads to 2D layer-by-layer growth and a smooth surface.…”
Section: Introductionmentioning
confidence: 99%